2023
DOI: 10.3389/fmed.2023.1092030
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effectiveness of One Health interventions against the zoonotic hookworm Ancylostoma ceylanicum

Abstract: Hookworm disease is a major global public health concern, annually affecting 500–700 million of the world's poorest people. The World Health Organization is targeting the elimination of hookworm as a public health problem by 2030 using a strategy of mass drug administration (MDA) to at-risk human populations. However, in Southeast Asia and the Pacific the zoonotic hookworm species, Ancylostoma ceylanicum, is endemic in dogs and commonly infects people. This presents a potential impediment to the effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Such a strategy would reduce the imperative for owners to have their puppies treated within the first 2 weeks postpartum to prevent egg shedding in this highly infected population (Gates and Nolan, 2009 ). Emphasizing the importance of public education to reduce roaming behaviour in dogs, remove and dispose of canine feces and wash hands regularly are also important means of controlling transmission (Macpherson et al ., 2022 ; Massetti et al ., 2022 ; Walker et al ., 2023 ). The presence of A. ceylanicum requires that further behavioural changes be adopted as well, such as wearing shoes outdoors and proper disposal of human and animal feces (Baker et al ., 2018 ; Nery et al ., 2019 ; Colella et al ., 2021 ; Walker et al ., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a strategy would reduce the imperative for owners to have their puppies treated within the first 2 weeks postpartum to prevent egg shedding in this highly infected population (Gates and Nolan, 2009 ). Emphasizing the importance of public education to reduce roaming behaviour in dogs, remove and dispose of canine feces and wash hands regularly are also important means of controlling transmission (Macpherson et al ., 2022 ; Massetti et al ., 2022 ; Walker et al ., 2023 ). The presence of A. ceylanicum requires that further behavioural changes be adopted as well, such as wearing shoes outdoors and proper disposal of human and animal feces (Baker et al ., 2018 ; Nery et al ., 2019 ; Colella et al ., 2021 ; Walker et al ., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Emphasizing the importance of public education to reduce roaming behaviour in dogs, remove and dispose of canine feces and wash hands regularly are also important means of controlling transmission (Macpherson et al, 2022;Massetti et al, 2022;Walker et al, 2023). The presence of A. ceylanicum requires that further behavioural changes be adopted as well, such as wearing shoes outdoors and proper disposal of human and animal feces (Baker et al, 2018;Nery et al, 2019;Colella et al, 2021;Walker et al, 2023). Further studies of Strongyloides spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is of particular concern since companion animals from the tropics, where hookworms and other geohelminths are most likely to be endemic, are constantly exposed and thus at risk of acquiring infections even after treatment (Dantas-Torres et al 2020). A recent modeling study revealed that human MDA with animal deworming of moderate coverage (20-50%) may reduce the human A. ceylanicum prevalence to less than 1% by 2030; increasing animal treatment coverage to at least 75% may result in transmission interruption (Walker et al 2023). The results of Walker et al (2023) indicate the importance of including animal reservoir hosts in control and preventive measures aimed at reducing the public health threat of zoonotic hookworms, such as A. ceylanicum.…”
Section: Treatment Control and Eliminationmentioning
confidence: 99%
“…A recent modeling study revealed that human MDA with animal deworming of moderate coverage (20-50%) may reduce the human A. ceylanicum prevalence to less than 1% by 2030; increasing animal treatment coverage to at least 75% may result in transmission interruption (Walker et al 2023). The results of Walker et al (2023) indicate the importance of including animal reservoir hosts in control and preventive measures aimed at reducing the public health threat of zoonotic hookworms, such as A. ceylanicum.…”
Section: Treatment Control and Eliminationmentioning
confidence: 99%